Prevalence and Recurrence Rates of Cytomegalovirus Infection Among Patients With Hematological Diseases in the Western Brazilian Amazon: A Cross-Sectional Study - Jean de Melo Silva; Renato Pinheiro-Silva; Regiane Costa de Oliveira; Carlos Eduardo de Castro Alves; Anderson Nogueira Barbosa; Gemilson Soares Pontes; Gemilson Soares Pontes; Gemilson Soares Pontes (Frontiers Media S.A., 2021)
Cytomegalovirus (CMV) is a worldwide distributed pathogen that may cause serious complications in patients with hematological diseases. This study aimed to serologically characterize CMV infection in patients suffering from hematological diseases in Amazonas state, Brazil. Serum samples from 323 patients were tested for the presence of anti-CMV IgM or IgG antibodies using an enzyme-linked immunosorbent assay. Positive samples for IgM were submitted to the IgG avidity test to differentiate primary infection from recurrent infection. An epidemiological questionnaire was administered to collect the sociodemographic information of the study population. The overall prevalence of CMV infection verified in this study was 91.3%. The highest rates were found in patients suffering from platelet disorders (94.5%), anemia (93.3%), or leukemia (91%). The study population was predominantly composed of individuals with low socioeconomic status. Blood transfusions were more common in patients with anemia or leukemia, but this variable was not correlated with the seropositivity for CMV infection. Measurement of IgG avidity in patients positive for anti-CMV IgM demonstrated a recurrent infection rate of 5.2% (17/323). Over 80% of recurrent infections occurred in patients with acute lymphocytic leukemia (ALL) or anemia. Our findings indicated that CMV infection is highly prevalent in patients from the western Brazilian Amazon who have hematological diseases. The prevalence observed progressively rose with increasing age, whereas anemia or ALL figured as risk factors for the recurrence of CMV infection.